The Application of Personal Education According to Thomas Lickona in the Daily Activities of Students of Assalam Islamic Boarding School for Islamic Teacher Training College, Surakarta, Central Java, Indonesia - Abu Darda; Muhammad Shofhan Amrullah Al Arif (Educan : Jurnal Pendidikan Islam, 2020)
Personality is a way of thinking and behaving among individuals in life, in the fields of family, community, nation and home. Thomas Aquina said, personality is related to moral knowledge, moral feelings, and moral behavior. These three factors, which help the personality to know the good, the desire to do good and do it, and one of the educational institutions that become the main reference in personality education is the institution. This institution is an educational institution that focuses on personal education and is one of the traditional institutions that focus on the study of Islamic sciences. This study aims to find out how to shape moral knowledge, moral feelings and moral behavior in the daily activities of students of Assalam Islamic Boarding School for Modern Islamic Education (PPMI). This research uses descriptive method and qualitative approach. Data obtained through interviews, monitoring and documentation. The results showed that personality education was applied at the Assalam Islamic Boarding Scholl for Modern Islamic Education through daily activities, where it included the cultivation of moral knowledge, the cultivation of moral sentiment and the cultivation of moral behavior. Instead, the method that supports student education is an integrated education process that includes study, education, discipline, and sports in slavery, and set good examples from school principals and teachers